Effect of Voacamine upon inhibition of hypoxia induced fatty acid synthesis in a rat model of methyln-nitrosourea induced mammary gland carcinoma - Lakhveer Singh (BMC Molecular and Cell Biology, 2021)
Abstract Background In the present study, fatty acid synthesis is targeted to combat mammary gland carcinoma by activating prolyl hydroxylase-2 with Voacamine alone and in combination with Tamoxifen. It was hypothesized that the activation of prolyl hydroxylase-2 would inhibit the hypoxia-induced fatty acid synthesis and mammary gland carcinoma. Mammary gland carcinoma was induced with a single dose administration of N-methyl-N-nitrosourea (50 mg/kg,i.p.) and treatment with Voacamine and Tamoxifen 15 days after carcinogen administration. Results At the end of the study, hemodynamic profiling of animals was recorded to assess the cardiotoxic potential of the drug. Blood serum was separated and subjected to nuclear magnetic resonance spectroscopy. Carmine staining and histopathology of mammary gland tissue were performed to evaluate the anti-angiogenic potential of the drug. The antioxidant potential of the drug was measured with antioxidant markers. Western blotting was performed to study the effect of the drug at the molecular level. Conclusion Results of the study have shown that Voacamine treatment stopped further decrease in body weight of experimental animals. The hemodynamic study evidenced that Voacamine at a low dose is safe in cardiac patients. Microscopic evaluation of mammary gland tissue documented the anti-angiogenic potential of Voacamine and Tamoxifen therapy. Perturbed serum metabolites were also restored to normal along with antioxidant markers. Immunoblotting of mammary gland tissue also depicted restoration of proteins of the hypoxic and fatty acid pathway. Conclusively, Voacamine and its combination with Tamoxifen activated prolyl hydroxylase-2 to combat mammary gland carcinoma.